The state of art regarding scientists, outreach and evolution: A systematic literature review design - Ambrósio, Susana (2021)
The study presented here is part of the COST Action “Building on scientific literacy in evolution towards scientifically responsible Europeans – EuroScitizen (CA17127), which aims to identify targeted strategies that will raise levels of scientific literacy in Europe using evolution as a model. Started in 2018, the research network is a European transdisciplinary community (almost 100 members from 31 countries) that brings together evolutionary biologists, educators, science communicators, media and policy makers to promote the public understanding of evolution. It is organized in five Working Groups: Assessment (WG1), Formal Education (WG2), Informal Education (WG3), Media (WG4) and Scientists (WG5). Within this last Working Group - Scientists (WG5) - the main tasks are (i) to undertake a systematic review of the ways in which researchers can be involved in outreach and develop a set of good practices that improve science and evolution literacy; (ii) to develop a standardized tools to enhance researcher engagement in outreach; (iii) to develop material to enhance researcher engagement in outreach (best practice guide) and (iv) to organize a joint meeting with existing initiatives on citizen science to explore citizen-science projects with an evolutionary focus. In this communication, we will focus on the design of the systematic literature review reporting the ways in which researchers can be involved in outreach. In other words, the literature review was designed to answer the research question: What does the research literature reveal about the status and practises of those conducting outreach in the field of evolutionary biology? The purpose of the review is, therefore, to establish what we know about how outreach is being delivered, where and by whom, as well as the motivation for doing outreach work. The research question was intended to be an open question that did not have any preconceived opinions or intended outcomes. This would allow us to review the widest range of literature available. We will present the ongoing systematic literature review process, which is based in a protocol (with nine steps) in order to ensure a carefully planned work and to promote consistent conduct by the research team, research integrity, accountability and transparency. Mainly, we will focus in the selection of documents (step 5), evaluation of the quality and relevance of the documents (step 6) and data processing (step 7) and how these last steps were made by using a digital qualitative analysis tool (webQDA). With this communication we intend to contribute positively to the discussion around systematic literature review and have the opportunity to improve our research methodology.